2016
DOI: 10.1038/srep37111
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Cyanobacterial DHDPS and DHDPR

Abstract: Lysine biosynthesis in bacteria and plants commences with a condensation reaction catalysed by dihydrodipicolinate synthase (DHDPS) followed by a reduction reaction catalysed by dihydrodipicolinate reductase (DHDPR). Interestingly, both DHDPS and DHDPR exist as different oligomeric forms in bacteria and plants. DHDPS is primarily a homotetramer in all species, but the architecture of the tetramer differs across kingdoms. DHDPR also exists as a tetramer in bacteria, but has recently been reported to be dimeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
4
25
0
Order By: Relevance
“…Affinity measurements using microscale thermophoresis (MST) were carried out employing a Monolith NT. 115 instrument (NanoTemper Technologies) as previously described (38,39). mIFNAR1-ECD and mIFNAR2-ECDC94S were labeled using the NHS RED NanoTemper labeling kit according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Affinity measurements using microscale thermophoresis (MST) were carried out employing a Monolith NT. 115 instrument (NanoTemper Technologies) as previously described (38,39). mIFNAR1-ECD and mIFNAR2-ECDC94S were labeled using the NHS RED NanoTemper labeling kit according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Even when multiple dapA genes have been annotated in a bacterium, such as in Agrobacterium tumefaciens, only one dapA gene has been shown to have bona fide DHDPS activity [36]. These enzymes have similar catalytic efficiencies, which are consistent with other DHDPS orthologues [16,36,51,52]. Alignments of multiple P. aeruginosa strains demonstrate that dapA2, dapA3 and dapA4 are universally present, whereas dapA1 is annotated in only 47% of 2.4 9 10 5 NR k cat /K M ASA (s À1 ÁM À1 ) 2.9 9 10 5 5.5 9 10 5 NR a Data obtained from [24], NR = not reported.…”
Section: Discussionmentioning
confidence: 60%
“…Recombinant proteins were expressed in E. coli BL21 (DE3) cells as hexa-histidine-tagged constructs and purified using immobilized metal affinity chromatography (IMAC) as previously described [16,63,64]. In brief, the synthetic genes coding for the P. aeruginosa proteins and the PaDHDPS2 mutants H56Q and H56K were purchased from Bioneer (Bioneer Pacific, Kew East, Vic., Australia) ligated in the pET28a expression vector.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Girish et al () found that DHDPR can also function as a dehydratase in addition to its role as an NAD(P)H‐dependent reductase. The structure of DHDPR has been determined from bacteria (including Gram‐positive; Girish, Navratna, & Gopal, ; Janowski, Kefala, & Weiss, ; Sagong & Kim, ) and Gram‐negative bacteria; Scapin, Reddy, Zheng, & Blanchard, ), cyanobacteria (Christensen et al, ), and plants (Griffin et al, ). These studies have shown that DHDPR is a homotetramer with a unique monomer unit, except for plant‐derived DHDPR.…”
Section: Introductionmentioning
confidence: 99%